MY PEDAGOGY – AN OUTLINE OF THE IDEA - Szulz, Roman (Acta Universitatis Nicolai Copernici. Pedagogika, 2023)
The text includes: a) a presentation of original idea of pedagogy; b) a presentation of the specifics of the author’s personal contribution to the development of pedagogy. Pedagogy is defined and characterised as a component and tool of the information system of education. The specifity of the author’s contribution to the development of pedagogy is showing the possibility of using the anthropological perspective in building the world-view foundation of education.